In vitro propagation and phytochemical screening from Peperomia pellucida L. Kunth. / Teoh Lydia - Teoh , Lydia (2019)
In the present study, regeneration of Peperomia pellucida L. Kunth. has been successfully developed through tissue culture technique. The main focus of the study was to assess the effects of plant growth regulators on in vitro propagation of shoot and callus induction. Additional assessment concerning the medicinal property of the plant was also examined. The best medium for seed germination was Murashige & Skoog (MS) basal medium. The optimum regeneration medium for Peperomia pellucida L. Kunth. shoot multiplication and shoot elongation was MS supplemented with 0.5 mg/L kinetin (KN) which resulted in 6.2 number of shoots with 0.7 cm in height. In combination of PGRs, MS medium supplemented with 1.5 mg/L benzylaminopurine (BA) and 1.5 mg/L kinetin (KN) with 10.3 shoots and 0.73 cm height. In combination of cytokinin and auxin, MS medium supplemented with 1.0 mg/L benzylaminopurine (BA) and 1.0mg/L Indole-3-acetic acid\ (IAA) induced 38.7 shoots. Meanwhile, the highest shoot elongation was observed on MS supplemented with 1.0 mg/L KN and 1.0 mg/L IAA (0.81 cm). When tested with Cytokinin and auxin, MS supplemented with 1.0 mg/L BA and 1.0 mg/L IAA resulted in 38.7 number of shoots. The highest shoot elongation was observed on MS supplemented with 1.0 mg/l KN and 1.0 mg/L IAA (0.81 cm). When comparing the shoot induction in different temperature and charcoal concentrations, MS medium supplemented with 15% charcoal at 13oC gave the highest shoot elongation (4.72 cm) and MS medium without charcoal showed the highest shoot multiplication with 2.60 number of shoots at 25oC which was insignificant with those grown at 13oC (2.53 shoots). For root induction, MS supplemented with 2.0 mg/l Indole-3-butric acid (IBA) gave the highest number (5.33) of root production. All the plantlets were successfully acclimatized with 85% survival rate under natural environment. Callus was successfully produced from leaf explants in MS medium with (0.1-0.6 mg/L) 2,4-D and resulted in formation of embryogenic callus. In vivo and in vitro plant methanol and ethanol extracts of Peperomia pellucida L. Kunth. were investigated by GC-MS and the presence of chemical compound such as apiol, phytol, hhenol, 9-octadecenoic acid (z) and caryophyllene was detected. All the plant extracts of Peperomia pellucida L. Kunth were effective against Staphylococcus aureus, Salmonella typhi, Escherichia coli and Pseudomonas aeruginosa. Methanol extract from in vitro plant showed the highest inhibition zone (12.5) against Staphylococcus aureus and followed by ethanol extract from in vitro plant shows (12 mm) inhibition zones against Salmonella typhi and Pseudomonas aeruginosa. Upon testing the extracts on human breast adenocarcinoma cell line (MCF-7) and human lung adenocarcinoma cell line (A549), in vitro ethanol extracts were toxic against proliferation of MCF-7 cells while in vitro methanol extracts were toxic for A549 cell. The reproducible protocol in this study has potential for establishment of selected and standardized plants suitable for the exploitation in various industries such pharmaceutical industries, agricultural, agrochemical industries and food industries.